2020
DOI: 10.1371/journal.pone.0233386
|View full text |Cite
|
Sign up to set email alerts
|

A high-salt/high fat diet alters circadian locomotor activity and glucocorticoid synthesis in mice

Abstract: Salt is an essential nutrient; however, excessive salt intake is a prominent public health concern worldwide. Various physiological functions are associated with circadian rhythms, and disruption of circadian rhythms is a prominent risk factor for cardiovascular diseases, cancer, and immune disease. Certain nutrients are vital regulators of peripheral circadian clocks. However, the role of a high-fat and high-salt (HFS) diet in the regulation of circadian gene expression is unclear. This study aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Many behavioral and physiological processes exhibit a 24-h rhythm that is regulated by the circadian rhythm system and can be altered by dietary components [10]. It has been reported that a diet high in fat and salt reduced locomotor activity and disrupted the diurnal rhythm of clock genes in the adrenal gland of mice [11]. An HSD shifts the phase of clock gene expression in peripheral tissues of mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many behavioral and physiological processes exhibit a 24-h rhythm that is regulated by the circadian rhythm system and can be altered by dietary components [10]. It has been reported that a diet high in fat and salt reduced locomotor activity and disrupted the diurnal rhythm of clock genes in the adrenal gland of mice [11]. An HSD shifts the phase of clock gene expression in peripheral tissues of mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a high-salt diet affected the circadian rhythm system and therefore caused sleep fragmentation. 38,39 Previous studies also proved that alcohol and caffeine could influence human circadian rhythms. 40,41 In addition, life stress could affect the hypothalamus-pituitary-adrenal axis in MD 42 and disrupt the circadian rhythm.…”
Section: Discussionmentioning
confidence: 97%
“…These triggers may also alter the expression of circadian clock genes in MD patients. For example, a high‐salt diet affected the circadian rhythm system and therefore caused sleep fragmentation 38,39 . Previous studies also proved that alcohol and caffeine could influence human circadian rhythms 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…In female mice, a high fat diet significantly decreased bmal1 expression in the ovary near the end of dark phase ( Yokoyama et al, 2020 ). StAR and CYP11A1 were downregulated at the beginning of light phase and CYP11B1 was downregulated at the beginning of dark phase.…”
Section: Differential Afferent Inputs To Peripheral and Scn Clocksmentioning
confidence: 99%